Myth and Ritual of Ine Pare: An Anthropolinguistic Study of Ende-Lio Ethnic Culture, Flores - Rero, Dentiana; Hasanuddin, Hasanuddin; Malihah , Elly; Sapriya, Sapriya; Ratmaningsih, Neiny (Jurnal Arbitrer, 2025)
This research on the myth and ritual of Ine Pare among the Ende-Lio community in Nida Village, Flores, Indonesia, aims to reveal how linguistic expressions encode local wisdom amid cultural marginalization. An ethnographic approach and linguistic anthropological theory are employed as the formal framework of the study. Data were collected through 16 weeks of participant observation and in-depth interviews with the traditional elder (Mosalaki) and five other key informants. Thematic data analysis found that the myth and ritual of Ine Mbu—the Rice Mother—represent a socio-ecological knowledge system supported by local rationality and religiosity. Socio-ecological knowledge is reflected in communal solidarity, equitable resource distribution, and environmental taboos. Local rationality is expressed through agricultural and nutritional knowledge. Religiosity is manifested in ancestor veneration, ritual obligations, and moral ethics enforced through communal sanctions. In this context, the Lio language, used in myths and ritual mantras, functions as the preserver and transmitter of these local wisdom values. The Nida-Ende community and its oral traditions and local wisdom remain relatively resilient due to geographic isolation. However, youth migration, digital and social media influx, and tourism commodification threaten these traditions. The implication of this research is strengthening linguistic anthropological scholarship regarding the relationship between oral traditions and local competencies (knowledge, skills, and attitudes) in sustaining ecological balance and social cohesion. These findings recommend undertaking cultural revitalization efforts, including documentation of local cultural heritage, integration of local wisdom into formal education curricula, and development of cultural tourism.